Matched-field tomography using an acoustic oceanographic buoy - Soares, C. (2014)
The Acoustic Oceanographic Buoy (AOB) is a light acoustic receiving device that is being developed in the framework of a joint research project and tested during the Maritime Rapid Environmental Assessment (MREA) sea trials. One of the AOB’s application is in Matched-Field Tomography (MFT) when a reduced number of receivers is available in opposition to traditional systems used in tomography. One problem of chief importance in MFT is the degree of uniqueness of the problem’s solution which is highly dependent on the number of receivers and on the number of free parameters. This paper studies the possibility of using matched-field processors with reduced ambiguity levels in comparison to conventional processors with application to acoustic data collected during the MREA sea trials. Two aspects are investigated: (a) the choice of an explicit broadband data model, where the exploitation of the spectral coherence of the acoustic field is seen as a mean to reduce the ambiguity level of the cost function used in the optimization; (b) conventional and high-resolution methods based on the proposed broadband model are implemented and compared.